Blended learning in lifelong adult education in the aspects of covid-19 epidemical restriction - Ābele, Lilita; Barute, Dina; Ulmane-Ozoliņa, Lāsma; Rivža, Baiba (Landscape Architecture and Art, 2021)
Digital skills are one of the most important skills that were highlighted in the times of COVID-19, including areas like landscape architecture. COVID-19 pandemic raised possibilities for blended-learning in adult education that were not used much before the pandemic. Data shows that Latvia’s inhabitants digital skills compared to the EU average is much lower and there is a need for innovative ways to attract lifelong learners to participate in skills’ advancement courses. At the end of 2020, a survey was conducted with the aim of the survey to find out the society's self-assessment of digital skills and the need to improve them for remote working. Results showed that a high number of respondents are willing to participate in blended learning courses and are eager to develop their digital skills.